2013
DOI: 10.1118/1.4815537
|View full text |Cite
|
Sign up to set email alerts
|

WE‐C‐WAB‐01: Intratumor Correlations of FDG, FLT, and Cu‐ATSM PET in Canine Tumors: Implications for Dose Painting

Abstract: Purpose: In dose painting, it is uncertain which of a tumor's biological properties should be targeted, and if plans for different tumor histologies are equally sensitive to the choice of biological target. This study characterizes the relationships between three potential biological targets ‐ glucose metabolism, proliferation, and hypoxia — in two different tumor histologies using PET/CT imaging. Methods: Twenty canine patients with sinonasal tumors (7 sarcomas and 13 carcinomas) were imaged using FDG, FLT, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mitigation of these errors can subsequently permit increasingly accurate radiation targeting of biological regions at greatest risk of treatment resistance, as well as modelling of regional imaging-based treatment response in tumour and normal tissue. These correlation studies have been reported on in disease sites that are less susceptible to respiratory motion (Bowen et al , 2012; Nyflot et al , 2012; Bradshaw et al , 2013), but have the potential to be translated to lung cancer. Furthermore, determination of motion-induced errors for different radiotherapy modalities, such as proton and heavy-ion therapy, could inform on their clinical suitability for different patient cases.…”
Section: Discussionmentioning
confidence: 78%
“…Mitigation of these errors can subsequently permit increasingly accurate radiation targeting of biological regions at greatest risk of treatment resistance, as well as modelling of regional imaging-based treatment response in tumour and normal tissue. These correlation studies have been reported on in disease sites that are less susceptible to respiratory motion (Bowen et al , 2012; Nyflot et al , 2012; Bradshaw et al , 2013), but have the potential to be translated to lung cancer. Furthermore, determination of motion-induced errors for different radiotherapy modalities, such as proton and heavy-ion therapy, could inform on their clinical suitability for different patient cases.…”
Section: Discussionmentioning
confidence: 78%